Taxation of Alcohol and Its Impact on Consumption - Kitová, Denisa (Opodatkowanie alkoholu i jego wpływ na konsumpcję, 2010)
Taxation of alcohol provides significant public revenues at low administrative costs. Reasons why specific types of goods are taxed more than others, and therefore it is necessary to preserve the tax and keep them at the highest level are the following: the effective increase in public revenues, addressing externalities and distributional implications. The examination of alcohol consumption from price changes is very difficult. Empirical studies using econometric methods provide estimates of price and income elasticities for various alcoholic beverages, especially wine, beer and spirits. Most of these studies indicate that the demand for alcohol, as well as for other goods, depends on price. The demand for spirits is the most sensitive to changes in prices compared with the demand for beer or wine.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 149, s. 144-151
Keywords: alcoholic; tax; elasticity; consumption